Dysbiosis-Associated Enteric Glial Cell Immune-Activation and Redox Imbalance Modulate Tight Junction Protein Expression in Gulf War Illness Pathology - Kimono, Diana; Sarkar, Sutapa; Albadrani, Muayad; Seth, Ratanesh; Bose, Dipro; Mondal, Ayan; Li, Yuxi; Kar, Amar N.; Nagarkatti, Mitzi; Nagarkatti, Prakash; Sullivan, Kimberly; Janulewicz, Patricia; et al. (Frontiers in Physiology, 2019)
About 14% of veterans who suffer from Gulf war illness (GWI) complain of some form of gastrointestinal disorder but with no significant markers of clinical pathology. Our previous studies have shown that exposure to GW chemicals resulted in altered microbiome which was associated with damage associated molecular pattern (DAMP) release followed by neuro and gastrointestinal inflammation with loss of gut barrier integrity. Enteric glial cells (EGC) are emerging as important regulators of the gastrointestinal tract and have been observed to change to a reactive phenotype in several functional gastrointestinal disorders such as IBS and IBD. This study is aimed at investigating the role of dysbiosis associated EGC immune-activation and redox instability in contributing to observed gastrointestinal barrier integrity loss in GWI via altered tight junction protein expression. Using a mouse model of GWI and in vitro studies with cultured EGC and use of antibiotics to ensure gut decontamination we show that exposure to GW chemicals caused dysbiosis associated change in EGCs. EGCs changed to a reactive phenotype characterized by activation of TLR4-S100β/RAGE-iNOS pathway causing release of nitric oxide and activation of NOX2 since gut sterility with antibiotics prevented this change. The resulting peroxynitrite generation led to increased oxidative stress that triggered inflammation as shown by increased NLRP-3 inflammasome activation and increased cell death. Activated EGCs in vivo and in vitro were associated with decrease in tight junction protein occludin and selective water channel aquaporin-3 with a concomitant increase in Claudin-2. The tight junction protein levels were restored following a parallel treatment of GWI mice with a TLR4 inhibitor SsnB and butyric acid that are known to decrease the immunoactivation of enteric glial cells. Our study demonstrates that immune-redox mechanisms in EGC are important players in the pathology in GWI and may be possible therapeutic targets for improving outcomes in GWI symptom persistence.